Diagnostically and Experimentally Useful Panel of Strains from the Burkholderia cepacia Complex - Mahenthiralingam, Eshwar (American Society for Microbiology, 2000)
Two new species, Burkholderia multivorans and Burkholderia vietnamiensis, and three genomovars (genomovars I, III, and IV) currently constitute the Burkholderia cepacia complex. A panel of 30 well-characterized strains representative of each genomovar and new species was assembled to assist with identification, epidemiological analysis, and virulence studies on this important group of opportunistic pathogens.